Competitive Behaviours In Response To Neighbours Of Two Woodland Plant Species - Murphy, Guillermo P. (My University, 2012)
Plants often grow in communities closely surrounded by neighbouring plants. Plants can actively and intensely compete for resources and also anticipate competition by sensing environmental cues from the presence and identity of neighbours. Moreover, it’s been proposed that the evolution of both increased and decreased competitive ability may serve as a mechanism for invasiveness. However, still little is known about how plants integrate competitive responses when sensing multiples cues of competition and which individual competitive traits respond to the identity of competitors. In addition, whether and why the evolution of competitive traits may contribute to the ability of introduced species to become invasive is also poorly understood.
Here I present a body of work that examined the competitive responses of a native and an invasive plant species to cues of competition and the identity of neighbours. I also examined how experimental manipulation of pot volume, to control belowground resources, affects plant growth and allocation. In one study I tested the competitive responses of the North American native, Impatiens pallida, to cues signalling the presence of neighbours above and belowground simultaneously in competitive environments composed of either siblings or strangers. I demonstrate that I. pallida can recognize siblings and shows more aggressive competitive behaviours towards strangers than kin.
In two other studies, I compared the competitive responses of the invasive and native ecotypes of Alliaria petiolata to changes in density, as well as to the presence and identity of neighbours. I found that invasive ecotypes produced less competitive phenotypes especially under high density. Moreover, I found that invasive ecotypes performed better when sharing rooting space with neighbours that were siblings.
Taken together, these results demonstrate the ability of these plant species to respond to the identity of neighbours and provide strong evidence in support of the evolution of reduced competitive ability hypothesis in invasive plant species potentially mediated by the action of kin selection in invasive ecotypes.
Keywords: plant kin recognition; plant competition; invasive species; evolution; behaviour; Alliaria petiolata; Behavior and Ethology; Evolution; Other Ecology and Evolutionary Biology; Plant Biology; Behavior and Ethology